VD_FINDINFO Décision / 2012 / 148 vom 24. November 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE COLLUSION, RISQUE DE FUITE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 222 CPP (CH), 227 CPP (CH), 228 al. 4 CPP (CH)